2014
DOI: 10.1134/s1070427214100012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical properties of Di- and trivalent metal-ammonium phosphates

Abstract: Data on the infl uence exerted by the synthesis conditions and by the nature and relative amounts of precursor reagents on the properties of metal-ammonium phosphates, promising as components of fi re-retardant and fi re-extinguishing additives, are summarized and analyzed. The manner in which the solution pH and nature and relative amounts of the reacting metal-, nitrogen-, and phosphorus-containing compounds affect the phase composition, solubility, aggregative state, and fundamental aspects of thermal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…), X (6) = (1, -1, 1), X (7) = (1, 1, -1), and X (8) = (1, 1, 1), we performed double observations, the results of which are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), X (6) = (1, -1, 1), X (7) = (1, 1, -1), and X (8) = (1, 1, 1), we performed double observations, the results of which are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Using the statistical functions of Excel spreadsheets, we obtained the estimates of the parameters of model ( 4): (7) In the determination of the adequacy of the obtained model observations (7) after the verification of the significance of its coefficients, we found that the model is adequate at the level of significance α = 0.05, and the coefficients at X 12 , X 13 , and X 23 are insignificant at a level of 0.05. If they are not taken into account, model ( 7) becomes very simplified, and it poorly describes the real phenomenological effect of fire-extinguishing efficiency due to a small number of experiments (N = 16), which does not allow us to estimate all of the seven significant coefficients of model (7). Therefore, to obtain more information in the estimation of unknown parameters at each point of the FFE spectrum, we carried out additional experiments to obtain data for y 13 -y 83 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often possible to find struvite in the composition of deposits on pipes diverting wastewater from livestock complexes [4]. There are many studies devoted to the methods of obtaining MAP [5,6,7,8]. Methods of obtaining MAP from agro-industrial wastewater have been developed.…”
Section: Introductionmentioning
confidence: 99%